Ill. bij gedicht "De natuurlijke historie der Christelijke regeeringsmeerderheid door L.M. Hermans - Hahn, Albert
Ill. bij gedicht "De natuurlijke historie der Christelijke regeeringsmeerderheid door L.M. Hermans.